Respiratory and lower limb muscle function in interstitial lung disease. (May 2016) - Panagiotou, Marios; Polychronopoulos, Vlasis; Strange, Charlie
Growing evidence suggests that respiratory and limb muscle function may be impaired in patients with interstitial lung disease (ILD). Importantly, muscle dysfunction could promote dyspnoea, fatigue and functional limitation all of which are cardinal features of ILD. This article examines the risk factors for skeletal muscle dysfunction in ILD, reviews the current evidence on overall respiratory and limb muscle function and focuses on the occurrence and implications of skeletal muscle dysfunction in ILD. Research limitations and pathways to address the current knowledge gaps are highlighted.